Explicit and Implicit Diversity Policy in the UK Film and Television Industries. Issue 1 (January 2020) - Newsinger, Jack; Eikhof, Doris Ruth
Abstract : This article adapts Jeremy Ahearne's conception of explicit and implicit cultural policy for a novel analysis of contemporary diversity policy in the British film and television industries. It demonstrates how distinguishing explicit and implicit diversity policy enables a better understanding of the policies, practices and strategic actions that impact workforce diversity outcomes. We provide an in-depth analysis of the different types of intervention that have been used to increase workforce diversity in the film and television industries in the UK since 2012. We then examine the arguments used to justify increased workforce diversity, focusing on the 'business case for diversity' and the logics which underpin it. Drawing on our own research as well as on industry reports and secondary literature, we examine the explicit and implicit workings of these policies and how they affect workforce diversity outcomes. We argue that the implicit/explicit dichotomy nuances and improves our understanding of the competing and contradictory forces that shape strategic courses of action regarding workforce diversity in the film and television industries, and provides a more nuanced conceptualisation of diversity policies and their outcomes.